If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 1x = 3x Solving 6 + 1x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 1x + -3x = 3x + -3x Combine like terms: 1x + -3x = -2x 6 + -2x = 3x + -3x Combine like terms: 3x + -3x = 0 6 + -2x = 0 Add '-6' to each side of the equation. 6 + -6 + -2x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 0 + -6 -2x = 0 + -6 Combine like terms: 0 + -6 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 16t^2+200t=-3 | | 3(x+4)=2x-12 | | 5-3[4-(3y-7)]= | | 136-(-11)= | | 7(-8+3h)=21h-49 | | 9m^3-7m^4+8m^7=0 | | 1/3p=2/5p+2/3 | | 6(x+2)/4=2x-5 | | 16t^2+200t=0 | | 8n-(2n+7)=17 | | 52+(-65)= | | .01(x+28)-.28=.01(8x+28) | | B=5A+4C | | (5/x)=(6/x^2)+1 | | -2(r+4)=-27 | | .4(3z+6)+20.4=.7(3z-6) | | 5/x=6/x^2+1 | | A=5B+4C | | x-2x+y/y | | 28-19= | | (2x+32)+6=x+26 | | t^2=6-t | | .3x-1=.1(x+10) | | f(4)=4+9.5 | | 3/10=x/2730 | | 1/m+1/2m=1/6 | | 2(2x+3)+2x=37 | | 7+5n=3n+5 | | x+x+3=5-2(x-5) | | 5/6y=7-11/12y | | x-6-(10x-8)= | | 3+8q=6+7q |